Ultra wide band circular ring patch with open ended slot and rectangular ground planer monopole antenna - Sambhe, V.K; Awale, R.N; Wagh, A (Proceedings of third International Conference on Computational Intelligence and Information Technology, 2013)
In this paper simple and low profile Wide Band Circular Ring Patch with open ended slot and Rectangular Ground Planar Monopole Antenna is proposed. The proposed antenna is simple to design and offer an effective control over the ultra wideband as well as extra wide band. By controlling the dimension of circular ring patch and optimizing the ground plane, the proposed candidate is suitable form 3.1 to 21 GHz. The simulation is done by using commercially available HL3D software version 15.2 [13]. The simulated VSWR is < 2 over the entire frequency band from 3.1 to 21GHz, approximately 17.9 GHz bandwidth. The antenna is simulated by different radius of the circular ring patch, rectangular ground plane dimension and the gap between the patch and ground. The radiation patterns indicate the suitability of this wireless candidate, like WiFi, WiMAX, X-band and other ultra wideband wireless communication applications.